Piezoelectric wave generation system for condition assessment of field water pipelines. Issue 5 (3rd September 2017) - Lee, Pedro; Tuck, Jeffrey; Davidson, Mark; May, Robert
ABSTRACT: The condition assessment of pipelines is central to the management of water systems but is only conducted sporadically due to the limited range and practical constraints of current technologies. This paper describes the successful international field trial of a new condition assessment approach that was tested in live water pipeline networks of large cities during peak water demand and traffic conditions. The system, referred to as PIPE SONAR (PCT/EP2015/059540), uses a piezoelectric actuator capable of generating customized, small amplitude (<0.4 m) pressure signals. The field trial involved 1600 individual field tests covering 31 sites of water networks in New Zealand and China, across nine different pipe materials and pipe diameters ranging from 100 mm to 600 mm. The results of the condition assessment were independently confirmed using hydrant tests, low frequency transient tests, and direct inspection through excavation.